FARTLEK TRAINING LEBIH MENINGKATKAN DAYA TAHAN KARDIOVASKULER DARI PADA INTERVAL TRAINING PADA SISWA PUTRA PESERTA EKSTRAKURIKULER BOLA BASKET SMA NEGERI 1 SUKAWATI - Mega Utama, Gusti Made Agung; Jawi, I Made; Ayu Dewi, Ni Nyoman; Weta, I Wayan; Muliarta, Made; Dwi Primayanti, I D A Inten (Sport and Fitness Journal; Volume 6, No.3, September 2018, 2019)
ABSTRACT Basketball is a big ball game that requires well cardiovascular endurance. Cardiovasculer endurance can be improved using interval training and fartlek training. This study aimed to determine the effect of interval training and fartlek training on cardiovascular endurance improvement. The study was a experimental that use randomized pretest posttest design group control that does in SMA Negeri 1 Sukawati. The sample of study was students of extracurricular basketball SMA Negeri 1 Sukawati, which were 22 students that divided into 2 groups. Both groups were given different training during 6 weeks with training frequency three times a week for one and a half months. The first group was given interval training and the second group was given fartlek training. Cardiovascular endurance was measured with a multistage fitness test (MFT). The result showed the mean of cardiovascular endurance between the groups after training was 41.66 ± 2.733 ml / kg / minute in the interval training group and was 48.92 ± 2.385 ml / kg / minute in the fartlek group. The cardiovascular endurance between both groups was significantly different (p<0.05), meaningful and have improvement. The conclusion is the interval training and fartlek training are able to improve cardiovascular endurance, however fartlek training is better than interval training in improving cardiovascular endurance. Therefore, it is advisable to use fartlek training to improve cardiovascular endurance for basketball players. Keywords: cardiovascular endurance, fartlek training, interval training